2021
DOI: 10.1093/tropej/fmab015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of SARS-CoV-2 Serology and Clinical Phenotype Amongst Hospitalised Children in a Tertiary Children’s Hospital in India

Abstract: Introduction Children usually present with minimal or no symptoms of COVID-19 infection. Antibody responses to SARS-CoV-2 in children from low- and middle-income countries (LMIC) have not been well described. We describe the prevalence of anti-SARS-CoV-2 antibodies and clinical phenotype of seropositive children admitted to a tertiary children’s hospital in South India. Methods To determine the seropositivity and describe the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
12
1
Order By: Relevance
“…One hospital-based study in Chennai had reported 19.6% prevalence in the age group of 1 month to 17 years. [13] Delhi Urban: During the first wave of the pandemic in India, the worst affected areas were the large urban areas, including Delhi. We collected the data during the second fortnight of March 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hospital-based study in Chennai had reported 19.6% prevalence in the age group of 1 month to 17 years. [13] Delhi Urban: During the first wave of the pandemic in India, the worst affected areas were the large urban areas, including Delhi. We collected the data during the second fortnight of March 2021.…”
Section: Resultsmentioning
confidence: 99%
“…One hospital-based study in Chennai had reported 19.6% prevalence in the age group of 1 month to 17 years. [13]…”
Section: Discussionmentioning
confidence: 99%
“…;Prakash et al, 2021b;Prakash et al, 2021c;Prakash et al, 2021d;Rafi et al, 2021;Ray et al, 2020;Satpati et al, 2020;Selvaraju et al, 2021;Sen et al, 2021;N. Sharma et al, 2020.;Siddiqui et al, 2020;Singhal et al, 2020;Siva Ganesa Karthikeyan et al, 2021;Velumani et al, 2021;Venkataraman et al, 2021) with 831,010 participants in the first wave (COVID-19sero survey-III (July 2021) -Tamil Nadu, 2021.; Misra et al, 2021;Selvaraju et al, personal communication;M. V. Murhekar, et al, 2021) with 74,369 participants in the second wave included in the systematic review and meta-analysis after full-text scrutiny (Figure 1, Supplementary table 1).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…In a study conducted by Venkatamaran et al in India, the authors evaluated humoral immune response associated with anti-SARS-CoV-2 antibody synthesis in hospitalised patients by comparing antibody titres between children with and without PIMS-TS [ 26 ]. Almost half of seropositive children had PIMS-TS.…”
Section: Discussionmentioning
confidence: 99%